Technology Of Forming A Multicomponent Organizational Structure Of A Continuous Pedagogical Education System - Georgiyevna Sergeeva, Marina (2021)
Successful results of all types of professional activities largely depend on the quality of training. At present, however, the acquired knowledge does not guarantee a university graduate stability of success throughout his/her career. Thus, the concept of lifelong education was gradually formed. From the previously established stereotype “education for life”, society is moving to the “education throughout life”. The traditional division of a person’s active life into the period of professional activity and study is blurring. There is a need for a transition to continuing professional education throughout life. One of the most important tasks for the management is to ensure the continuous development and survival of the organizations. Such a task is also vital for the institutions of additional professional education. With the transition to the newly established market relations, in the Russian Federation, the conditions for the operation of the system of additional professional education have changed significantly. First of all, a market for services in the field of additional professional education has emerged, where a large number of organizations of various forms of ownership operate, creating strong competition. In these conditions, the maximum consideration of different factors influencing on the additional professional education institutions, as well as the choice of a management strategy, is an important condition for their successful development and competitiveness. The demand of society for an effective system of additional vocational education determines its place and role in the state policy in relation to the development of human resources. At the same time, it is necessary to take into account the challenges of the labor market, the increasing needs of production, the real sector of the economy, the non-production sphere in qualified workers, specialists, managers, as well as training and re-training of unemployed citizens.